Efecto de los extractos de croton alnifolius (tunga) frente a las cepas de salmonella typhi y escherichia coli in vitro - Morillo Ramos, Victoria Giovanna (2011)
The study aimed to "Determine the antibacterial activity of extracts from the leaves of Croton Alnifolius (Tunga) against strains of Salmonella typhi and Escherichia coli in vitro. In this study, we used the diffusion method of Kirby Bauer amended, which was given to concentrations of 8, 16, 24, and 32 μg in 10, 15, 30 and 40 μl respectively, of the hexane, ethanol and aqueous the leaves of Croton alnifolius (Tunga) strains of Salmonella typhi and Escherichia coli, allowed to incubate for a period of 24 hours and then proceeded to read out. The readings of the halos of inhibition showed that concentrations from 16 μg in 15 μl hexanol extract from the leaves of Croton Alnifolius (Tunga), effective antibacterial effect was observed for both Salmonella typhi and Escherichia coli. However, in ethanol and aqueous extracts of leaves of Croton Alnifolius (Tunga) only got effectiveness, the maximum concentration of 32 μg administered in 40 μl, in both strains. From these results we conclude the following: That extracts from Croton Alnifolius (Tunga) have effective antibacterial activity concentration of 32 μg in 40 μl against Salmonella typhi and Escherichia coli in vitro